2013
DOI: 10.1002/cbic.201300296
|View full text |Cite|
|
Sign up to set email alerts
|

Incorporation of Nucleoside Probes Opposite O6‐Methylguanine by Sulfolobus solfataricus DNA Polymerase Dpo4: Importance of Hydrogen Bonding

Abstract: O6-Methylguanine (O6-MeG) is a mutagenic DNA lesion, arising from the action of methylating agents on guanine (G) in DNA. Dpo4, an archaeal low-fidelity Y-family DNA polymerase involved in translesion DNA synthesis (TLS), is a model for studying how human Y-family polymerases bypass DNA adducts. Previous work showed that Dpo4-mediated dTTP incorporation is favoured opposite O6-MeG rather than opposite G. However, factors influencing the preference of Dpo4 to incorporate dTTP opposite O6-MeG are not fully defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Nucleoside analogs have been used to interrogate TLS and elucidate chemical interactions that impact DNA replication on damaged DNA substrates. For O 6 -alkylguanine adducts, the use of synthetic nucleoside triphosphates in a TLS study showed how hydrogen bonding is important for the fidelity observed by Dpo4 to bypass O 6 -MeG . Further, nucleoside analogs with aromatic hydrocarbon functionality can stabilize duplexes containing O 6 -alkylguanine DNA adducts through base stacking interactions. , Recently, we communicated that the rates and fidelities of Dpo4-mediated synthesis past terminal base pairs containing O 6 -BnG placed opposite of nucleoside analogs differ depending on nucleobase size and shape for the nucleobase-surrogates BIM and Peri (Figure B).…”
mentioning
confidence: 99%
“…Nucleoside analogs have been used to interrogate TLS and elucidate chemical interactions that impact DNA replication on damaged DNA substrates. For O 6 -alkylguanine adducts, the use of synthetic nucleoside triphosphates in a TLS study showed how hydrogen bonding is important for the fidelity observed by Dpo4 to bypass O 6 -MeG . Further, nucleoside analogs with aromatic hydrocarbon functionality can stabilize duplexes containing O 6 -alkylguanine DNA adducts through base stacking interactions. , Recently, we communicated that the rates and fidelities of Dpo4-mediated synthesis past terminal base pairs containing O 6 -BnG placed opposite of nucleoside analogs differ depending on nucleobase size and shape for the nucleobase-surrogates BIM and Peri (Figure B).…”
mentioning
confidence: 99%
“…The key artificial nucleotide used for this study was a heterocyclic imidic nucleotide that is inserted opposite O 6 -CMG but not G, therefore, marking the presence of O 6 -CMG. This approach builds on previous research concerning the interaction of artificial nucleotides with DNA adducts and polymerase-mediated amplification of damaged DNA. The artificial nucleotide was selectively inserted opposite O 6 -CMG by a bypass-proficient KlenTaq mutant DNA Pol and required to efficiently extend a primer annealed to a DNA template containing O 6 -CMG, promoting DNA synthesis past O 6 -CMG. While the strategy has the potential to target any DNA sequence by employing the corresponding complementary sequence as a DNA primer, increased sensitivity is required to enable its utilization to interrogate defined genomic sequences for O 6 -CMG formation and persistence in biological samples to relate with CRC mutation landscapes.…”
Section: Strategies To Map O 6-cmg In Dnamentioning
confidence: 99%
“…TLS is characterized by a nucleotide insertion and subsequent extension step to replicate past DNA damage. To understand chemical factors impacting nucleotide selection for insertion opposite O 6 -MeG, we tested the ability of the archaeal DNA polymerase Dpo4 to insert nucleoside analogues opposite O 6 -MeG . We found that synthetic dNTPs with a wide range of size and hydrogen bonding capacities were generally inserted with a higher frequency opposite G than O 6 -MeG.…”
Section: Synthetic Nucleosides As Probes To Investigate Translesion D...mentioning
confidence: 99%